Factors Influencing College Student’s Financial Literacy - Lady, Lady (Journal of Global Business and Management Review, 2019)
Awareness of financial knowledge in this era, especially college students, is still scarce. College students are one part of society which increasing each year in numbers and would have strong impact on the economy of a country. College student is one levelbefore get into the working level, which means they have to be more able to depend on their own self in managing their own finances. This study?s purpose is to analyze factors which affect financial literacy of college students in Indonesia. The independent variables used are money management, financial behavior, influence, attitude, and investment. This study survey usedgoogle form which has 28 questions. The sample of this study is 350 college students taken randomly. The data tested by using SPSS program. This study results proved that all of the independent variables affect significantly positive on the financial literacy.